2018
DOI: 10.1016/j.pharep.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lipoic acid and n -3 long-chain polyunsaturated fatty acid on the liver ovariectomized rat model of menopause

Abstract: The results suggest that the antioxidant response varies among evaluated supplementations and all supplements were able to alter enzymatic and non-enzymatic antioxidants in the livers of ovariectomized rats. DHA presented the most evident antioxidant effect, decreasing protein and lipid damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The ovariectomy-induced menopause model in female rats is widely used to study biological processes and test new interventions that can minimize harmful effects associated with menopause (3,24,32). The experimental model most commonly used to observe the menopause period is a bilateral ovarian surgery (34,35). OS is a condition characterized by an imbalance between pro-oxidant molecules and antioxidant defenses, including reactive oxygen and nitrogen species.…”
Section: Resultsmentioning
confidence: 99%
“…The ovariectomy-induced menopause model in female rats is widely used to study biological processes and test new interventions that can minimize harmful effects associated with menopause (3,24,32). The experimental model most commonly used to observe the menopause period is a bilateral ovarian surgery (34,35). OS is a condition characterized by an imbalance between pro-oxidant molecules and antioxidant defenses, including reactive oxygen and nitrogen species.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, ovariectomized models are more commonly used [ 28 , 29 ]. Several studies have also shown that estrogen receptor alpha (ER α ) is associated with weight control and lipid accumulation [ 7 , 30 ]. As in the study of Palmisano and Koshy et al, fatty liver is induced in ovariectomized rodents, and the improvement effect of fatty liver has been verified when treated with similar estrogens such as estrogen or phytoestrogens [ 8 , 10 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Menopausal women experience significant changes in hormones due to a decrease in the female hormone estrogen. Postmenopausal changes in female hormones cause various symptoms such as osteoporosis and cardiovascular disease, thereby changing the quality of life [2,[5][6][7][8]. In menopause, estrogen is decreased specifically, cholesterol is accumulated in the body, and fatty liver is induced.…”
Section: Introductionmentioning
confidence: 99%
“… 123 It is a key cofactor in the construction of vital metabolic multienzyme complexes, including pyruvate dehydrogenase and the glycine cleavage system. 123 It is also a strong antioxidant 1 , 119 , 124 , 125 and anti-inflammatory 109 , 119 , 125 agent capable of activating and modulating signal transduction pathways, 109 , 119 , 126 upregulating the expression of nerve growth factor, and augmenting the conduction velocity of motor nerves. 127 …”
Section: α-Lipoic Acid L -Carnitine and Butyratementioning
confidence: 99%